Resin composition and application thereof
By adding titanic acid and inorganic nitrogen -containing compounds that are treated with silane coupling agent on the surface of the silantine plywood, the problem of limited application of polyachol resin in the field of high thermal conductivity has been solved. A constant resin composition is suitable for high heat -resistant and high -frequency antenna base modules.
Patent Information
- Application Number
- CN202411501191.X
- Authority / Receiving Office
- CN · China
- Patent Type
- Applications(China)
- Current Assignee / Owner
- Filing Date
- 2024-10-25
- Publication Date
- 2025-01-28
AI Technical Summary
Polystyrene alcohol resins are limited in the field of high thermal conductivity, because they have poor solvent resistance and poor compatibility, and the dispersion of inorganic fillers does not meet the requirements.
A resin composition, including dual -key polyachol resin, cross -linked agent, titanate inorganic compounds treated with silane coupling agents and mixtures of inorganic nitrogen -containing compounds, as well as optional hydrocarbons.
Improving the compatibility between each component and the decentralization of inorganic fillers, improved the thermal conductivity and dielectric constant of the resin composition, and obtained the resin composition with high heat resistance, high DK, high heat conductivity. Suitable for high heat -resistant high -frequency antenna substrate modules.
Smart Images

Figure BDA0005103844280000021 
Figure BDA0005103844280000051 
Figure BDA0005103844280000061
Abstract
Description
Technical Field
[0001] The present invention relates to the technical field of electronic materials, and in particular to a resin composition and application thereof. Background Art
[0002] In recent years, with the development of the electronic information industry, the speed and volume of information processing have increased significantly. Terminals and base stations represented by 5G communications require faster signal transmission speeds and lower signal loss, which puts higher requirements on the comprehensive performance of laminates.
[0003] The presence of benzene rings in polyphenylene ether resin increases the barrier to rotation within its molecular chain segments, resulting in the rigidity of the macromolecular chain. Due to its regular and symmetrical structure, polyphenylene ether resin has a higher glass transition temperature. At the same time, since polyphenylene ether resin molecules do not contain polar groups, they have excellent electrical properties, low dielectric constant and dielectric loss, and are therefore widely used in circuit board materials. However, polyphenylene ether resin has poor solvent resistance and compatibility, and requires the addition of a large amount of inorganic fillers in the field of high thermal conductivity. However, the dispersibility of inorganic fillers with smaller particle sizes in the polyphenylene ether system seriously fails to meet the requirements, which greatly limits the application of polyphenylene ether resin in circuit boards for high-frequency circuits with high thermal conductivity. Summary of the invention
[0004] The purpose of the present invention is to provide a resin composition and application thereof.
[0005] To achieve the above-mentioned purpose, the present invention adopts the following technical scheme: a resin composition, comprising:
[0006] Double bond-containing polyphenylene ether resin: 100 parts by weight;
[0007] Cross-linking agent: 5-80 parts by weight;
[0008] Inorganic filler: 10-250 parts by weight, wherein the inorganic filler is a mixture of a titanate inorganic compound and an inorganic nitrogen-containing compound, wherein the titanate inorganic compound is a titanate inorganic compound surface-treated with a silane coupling agent, and the inorganic nitrogen-containing compound is an inorganic nitrogen-containing compound surface-treated with a silane coupling agent, and the silane coupling agent contains a vinyl group, an allyl group, a methacrylate group or an acrylate group;
[0009] Hydrocarbon resin: 0-60 parts by weight.
[0010] As a further improvement of the present invention, the titanate inorganic compound is selected from at least one of calcium titanate, strontium titanate, barium titanate, lead titanate, magnesium titanate, lead zirconate titanate, and lanthanum lead zirconate titanate.
[0011] As a further improvement of the present invention, the inorganic nitrogen-containing compound is selected from at least one of aluminum nitride, boron nitride and silicon nitride.
[0012] As a further improvement of the present invention, the silane coupling agent used to treat the titanate inorganic compound and the silane coupling agent used to treat the nitrogen inorganic compound contain the same reactive group.
[0013] As a further improvement of the present invention, the silane coupling agent is at least one of the following structures:
[0014]
[0015] As a further improvement of the present invention, the D50 of the inorganic nitrogen-containing compound is 3μm-20μm, and the D50 of the titanate inorganic compound is 0.1μm-5μm; or, the D50 of the inorganic nitrogen-containing compound is 5μm-10μm, and the D50 of the titanate inorganic compound is 1μm-5μm.
[0016] As a further improvement of the present invention, the hydrocarbon resin is selected from at least one of polybutadiene, polybutadiene-styrene copolymer, divinylbenzene, styrene, BVPE, butadiene / divinylbenzene / styrene copolymer, butadiene / divinylbenzene copolymer, and divinylbenzene / BVPE copolymer.
[0017] As a further improvement of the present invention, the double-bond-containing polyphenylene ether resin and the silane coupling agent contain the same unsaturated double-bond group.
[0018] As a further improvement of the present invention, the crosslinking agent is selected from at least one of triallyl isocyanate monomers, triallyl isocyanate prepolymers, butadiene monomers, styrene monomers, pentadiene monomers, dicyclopentadiene dimethacrylate monomers, norbornene monomers, and cyclopentadiene monomers.
[0019] To achieve the above-mentioned object of the invention, the present invention also provides a use of the above-mentioned resin composition in prepregs, copper-clad laminates, insulating films, insulating boards, circuit substrates and electronic devices.
[0020] Beneficial effects: Compared with the prior art, the present invention has the following advantages:
[0021] The resin composition of the present invention adds an inorganic nitrogen-containing compound and a titanate inorganic compound surface-treated with a silane coupling agent to a high-heat-resistant double-bond polyphenylene ether resin system, which can further improve the thermal conductivity and Dk value (dielectric constant) of the resin composition on the basis of improving the compatibility between the components and the dispersibility of the inorganic filler in the resin system; at the same time, the two inorganic fillers of different types are used in combination with each other, which can not only increase the filling amount of the inorganic filler, but also inhibit the decrease in the Dk value and thermal conductivity of the resin composition, and can obtain a resin composition with excellent high heat resistance, high Dk, and high thermal conductivity, thereby finally obtaining a cured product with high heat resistance, high thermal conductivity, and high dielectric constant, thereby obtaining a cured product with relatively excellent comprehensive performance, which can be well applied in the field of high-heat-resistant high-frequency antenna substrate modules, especially can meet the requirements of millimeter-wave antenna modules. DETAILED DESCRIPTION
[0022] The following is a specific implementation of the embodiment of the present invention. It should be pointed out that for ordinary technicians in this field, several improvements and modifications can be made without departing from the principles of the embodiment of the present invention. These improvements and modifications are also considered to be within the scope of protection of the embodiment of the present invention.
[0023] The terms “comprising” and “containing” in the present specification mean that other components may be contained in addition to the components mentioned above, and these other components can impart different characteristics to the resin composition.
[0024] The present invention provides a resin composition, comprising:
[0025] Double bond-containing polyphenylene ether resin: 100 parts by weight;
[0026] Cross-linking agent: 5-80 parts by weight;
[0027] Inorganic filler: 10-250 parts by weight, wherein the inorganic filler is a mixture of a titanate inorganic compound and an inorganic nitrogen-containing compound, wherein the titanate inorganic compound is a titanate inorganic compound surface-treated with a silane coupling agent, and the inorganic nitrogen-containing compound is an inorganic nitrogen-containing compound surface-treated with a silane coupling agent, and the silane coupling agent contains a vinyl group, an allyl group, a methacrylate group or an acrylate group;
[0028] Hydrocarbon resin: 0-60 parts by weight.
[0029] The resin composition of the present invention adds an inorganic nitrogen-containing compound and a titanate inorganic compound surface-treated with a silane coupling agent to a high-heat-resistant double-bond polyphenylene ether resin system, which can further improve the thermal conductivity and Dk value (dielectric constant) of the resin composition on the basis of improving the compatibility between the components and the dispersibility of the inorganic filler in the resin system; at the same time, the two inorganic fillers of different types are used in combination with each other, which can not only increase the filling amount of the inorganic filler, but also inhibit the decrease in the Dk value and thermal conductivity of the resin composition, and can obtain a resin composition with excellent high heat resistance, high Dk, and high thermal conductivity, thereby finally obtaining a cured product with high heat resistance, high thermal conductivity, and high dielectric constant, thereby obtaining a cured product with relatively excellent comprehensive performance, which can be well applied in the field of high-heat-resistant high-frequency antenna substrate modules, especially can meet the requirements of millimeter-wave antenna modules.
[0030] It should be noted that the cured product in the present invention can be understood as a prepreg, an insulating film, an insulating board, a copper-clad laminate, a circuit substrate, an electronic device, and the like.
[0031] In some optional implementations, the titanate inorganic compound is 5-100 parts by weight, and the inorganic nitrogen-containing compound is 5-150 parts by weight.
[0032] Specifically, the titanate inorganic compound is selected from at least one of calcium titanate, strontium titanate, barium titanate, lead titanate, magnesium titanate, lead zirconate titanate, and lead lanthanum zirconate titanate. The titanate inorganic compound is a high Dk inorganic filler and can increase the Dk value of the resin composition.
[0033] In a specific embodiment, the titanate inorganic compound is selected from calcium titanate, barium titanate and strontium titanate.
[0034] In some optional embodiments, the D50 of the inorganic titanate compound is 0.1 μm-10 μm, that is, the median particle size of the inorganic titanate compound is 0.1 μm-10 μm.
[0035] The inorganic nitrogen-containing compound is selected from at least one of aluminum nitride, boron nitride and silicon nitride. The inorganic nitrogen-containing compound is a high thermal conductivity inorganic filler and can improve the thermal conductivity of the resin composition.
[0036] In some optional embodiments, the D50 of the inorganic nitrogen-containing compound is 1 μm-25 μm, that is, the median particle size of the inorganic nitrogen-containing compound is 1 μm-25 μm.
[0037] Specifically, when the D50 of the inorganic nitrogen-containing compound is 3μm-20μm, the D50 of the titanate inorganic compound is 0.1μm-5μm. When the D50 of the inorganic nitrogen-containing compound is 5μm-10μm, the D50 of the titanate inorganic compound is 1μm-5μm. That is, inorganic fillers of different types and particle sizes are mixed and applied to the resin composition, and the inorganic fillers with smaller particle sizes will be dispersed into the inorganic fillers with larger particle sizes, which not only increases the filling amount of the inorganic filler, but also maintains excellent dispersibility and excellent high dielectric constant and high thermal conductivity of each, so that the resin composition has excellent high dielectric constant and high thermal conductivity. At the same time, with high heat-resistant resin, it can be well used in the field of high heat-resistant high-frequency antenna substrate modules, meeting the requirements of high heat resistance, high Dk value and high thermal conductivity of 5G millimeter wave antenna modules.
[0038] In some optional embodiments, the silane coupling agent is at least one of the following structures:
[0039]
[0040]
[0041] Specifically, the vinyl silane coupling agent can be selected from at least one of the following: KBM-1003, KBM-1403 or KBE-1003 manufactured by Shin-Etsu Chemical, Z-6300, Z-6519, Z6825 or Z-6075 manufactured by Dow Corning, VTMO, VTEO or VTMOEO manufactured by Evonik. The methacrylate silane coupling agent can be selected from at least one of the following: KBM-503 or KBE-503 manufactured by Shin-Etsu Chemical, A-174 or Y-9936 manufactured by Momentive.
[0042] In a preferred embodiment, the silane coupling agent for treating the titanate inorganic compound contains the same reactive group as the silane coupling agent for treating the inorganic nitrogen-containing compound. The compatibility between the two inorganic fillers can be improved, which not only increases the filling amount of the inorganic filler, but also maintains excellent dispersibility and excellent high dielectric constant and high thermal conductivity of each, so that the resin composition has excellent high dielectric constant and high thermal conductivity. At the same time, with high heat-resistant resin, it can be well applied in the field of high heat-resistant high-frequency antenna substrate modules, meeting the requirements of high heat resistance, high Dk value and high thermal conductivity of 5G millimeter wave antenna modules.
[0043] In a specific embodiment, the silane coupling agent for treating the titanate inorganic compound and the inorganic nitrogen-containing compound is styrene-based, and the polyphenylene ether is styrene-based polyphenylene ether resin.
[0044] In a preferred embodiment, the double-bond polyphenylene ether resin and the silane coupling agent contain the same unsaturated double-bond group, so that the compatibility between the double-bond polyphenylene ether resin, the titanate inorganic compound and the inorganic nitrogen-containing compound is good, the addition amount of the titanate inorganic compound and the inorganic nitrogen-containing compound in the resin composition is effectively increased, and the decrease in the Dk and thermal conductivity of the resin composition is suppressed, while lower dielectric loss is obtained, so that the final cured product has a better balance in terms of dielectric constant, dielectric loss, thermal conductivity, heat resistance and peel strength.
[0045] Specifically, the double-bond-containing polyphenylene ether resin contains a vinyl group, an allyl group or a methacrylate group.
[0046] In some optional embodiments, the double bond-containing polyphenylene ether resin is selected from at least one of the following structures:
[0047]
[0048] Wherein, R1, R2, R3, R4, R5, R6, R7, and R8 in the above-mentioned double-bond polyphenylene ether resin structure are independently selected from hydrogen or any one of C1-C5 alkyl groups, and Y is no connecting bond, -O-, methylene, ethylene, -S-,
[0049] In one specific embodiment, the double bond-containing polyphenylene ether resin is selected from Sabic SA9000 or OPE-2St manufactured by Mitsubishi.
[0050] Specifically, the hydrocarbon resin is selected from at least one of polybutadiene, polybutadiene-styrene copolymer, divinylbenzene, styrene, BVPE, butadiene / divinylbenzene / styrene copolymer, butadiene / divinylbenzene copolymer, and divinylbenzene / BVPE copolymer.
[0051] The content of the hydrocarbon resin is 0-60 parts by weight, such as 0 parts by weight, 10 parts by weight, 20 parts by weight, 30 parts by weight, 40 parts by weight, 50 parts by weight, 60 parts by weight and specific values between the above values. Due to the limited space and simplicity, the present invention will no longer exhaustively list the specific values included in the range. It can be seen that when the content of the hydrocarbon resin is 0 parts by weight, the resin composition does not contain the hydrocarbon resin.
[0052] Preferably, the content of the hydrocarbon resin is 5-40 parts by weight, such as 5 parts by weight, 10 parts by weight, 15 parts by weight, 20 parts by weight, 25 parts by weight, 30 parts by weight, 35 parts by weight, 40 parts by weight and specific points between the above values. Due to space limitations and for the sake of simplicity, the present invention no longer exhaustively lists the specific points included in the range.
[0053] The crosslinking agent is selected from at least one of triallyl isocyanurate monomer (TAIC), triallyl isocyanate prepolymer, butadiene monomer, styrene monomer, pentadiene monomer, dicyclopentadiene dimethacrylate monomer, norbornene monomer, and cyclopentadiene monomer.
[0054] In a specific embodiment, the crosslinking agent is triallyl isocyanurate monomer, dicyclopentadiene dimethacrylate monomer or a combination thereof.
[0055] Specifically, the structural formula of triallyl isocyanurate monomer is
[0056]
[0057] The structural formula of dicyclopentadiene dimethacrylate monomer is
[0058]
[0059] The triallyl isocyanurate monomer may be TAIC manufactured by Mitsubishi Chemical, TAIC manufactured by Evonik, or TAIC manufactured by Nippon Chemical. The dicyclopentadiene dimethacrylate monomer may be A-DCP manufactured by Shin-Nakamura Chemical or DCP-A manufactured by Kyoeisha Chemical.
[0060] Furthermore, the resin composition further comprises 0.01-10 parts by weight of a catalyst, wherein the catalyst is at least one selected from imidazoles, pyridines, organic phosphorus or metal salts.
[0061] Preferably, the imidazole catalyst is selected from at least one of 4-dimethylaminopyridine, 2-methylimidazole, 2-ethyl-4-methylimidazole, 2-phenylimidazole, modified imidazole and zinc octoate.
[0062] Preferably, the organophosphorus is selected from triphenylphosphine.
[0063] Furthermore, the resin composition also contains 5-60 parts by weight of a flame retardant, so that the final cured product has a certain flame retardant effect.
[0064] The flame retardant is selected from at least one of a bromine flame retardant, a phosphorus flame retardant, a nitrogen flame retardant, an organic silicon flame retardant, and an organic metal salt flame retardant.
[0065] Specifically, the bromine flame retardant is selected from decabromodiphenyl ether, decabromodiphenyl ethane, brominated styrene or tetrabromophthalamide; the phosphorus flame retardant is selected from inorganic phosphorus, condensed phosphate ester, phosphoric acid, hypophosphite, phosphorus oxide, 9,10-dihydro-9-oxa-10-phosphaphenanthrene-10-oxide (DOPO), 10-(2,5-dihydroxyphenyl)-9,10-dihydro-9-oxa-10-phosphaphenanthrene-10-oxide (DOPO-HQ), (k is an integer from 1 to 5), 10-phenyl-9,10-dihydro-9-oxa-10-phosphaphenanthrene-10-oxide, tris(2,6-dimethylphenyl)phosphine, phosphazene, modified phosphazene.
[0066] In a preferred embodiment, the flame retardant is a condensed phosphate ester, a hypophosphite or a bis-DOPO compound.
[0067] Furthermore, the present invention also provides a use of the above resin composition in prepregs, copper-clad laminates, insulating films, insulating boards, circuit substrates and electronic devices.
[0068] Specifically, the present invention further provides a prepreg, which comprises a reinforcing material and the above-mentioned resin composition, wherein the resin composition is impregnated on the reinforcing material.
[0069] The reinforcing material may be selected from at least one of natural fibers, organic synthetic fibers, organic fabrics, and inorganic fabrics.
[0070] Preferably, the reinforcing material is glass fiber cloth. Among the glass fiber cloth, open fiber cloth or flat cloth is preferably used. More preferably, the glass fiber cloth is E glass fiber cloth, S glass fiber cloth, T glass fiber cloth or Q glass fiber cloth.
[0071] In addition, when the reinforcing material is glass fiber cloth, the glass fiber cloth generally needs to be chemically treated to improve the interface bonding between the resin composition and the glass fiber cloth. The main method of the chemical treatment is coupling agent treatment, and the coupling agent used is preferably epoxy silane coupling agent or amino silane coupling agent, so that the reinforcing material has good water resistance and heat resistance.
[0072] Specifically, the method for preparing the prepreg comprises the following steps:
[0073] Dissolving the resin composition with a solvent to prepare a resin composition glue solution;
[0074] The reinforcing material is immersed in the above-mentioned resin composition glue solution, and then the immersed reinforcing material is taken out and heated and dried to obtain the prepreg.
[0075] In a specific embodiment, the impregnated reinforcing material is baked at 100° C. to 180° C. for 1 min to 15 min, and the prepreg is obtained after drying.
[0076] Specifically, the solvent can be selected from at least one of acetone, butanone, methyl isobutyl ketone, N,N-dimethylformamide, N,N-dimethylacetamide, ethylene glycol methyl ether, propylene glycol methyl ether, benzene, toluene, xylene, and cyclohexane.
[0077] The present invention does not specifically limit the amount of solvent used in preparing the prepreg. The amount of solvent added is selected by those skilled in the art based on their own experience, as long as the obtained resin composition glue has a viscosity suitable for use.
[0078] The present invention also provides a copper-clad laminate, which comprises at least one of the above-mentioned prepregs and a metal foil formed on at least one side of the prepreg. When the copper-clad laminate comprises only one of the above-mentioned prepregs, the metal foil is arranged on at least one side of the surface of the prepreg. When the copper-clad laminate comprises at least two of the above-mentioned prepregs, the at least two prepregs are stacked and bonded together by heating and pressurizing to form a combined sheet, and then the metal foil is bonded on one side or both sides of the combined sheet by heating and pressurizing to form the copper-clad laminate.
[0079] Specifically, the preparation steps of the copper-clad laminate are as follows: a single side or double sides of a prepreg is coated with metal foil, or at least two prepregs are stacked to form a combined sheet, a single side or double sides of the combined sheet is coated with metal foil, and hot pressing is performed to obtain a copper-clad laminate.
[0080] The pressing conditions of the copper-clad laminate are: pressing at a pressure of 0.2 to 2 MPa and a temperature of 150° C. to 250° C. for 1 to 4 hours.
[0081] Specifically, the number of the prepregs can be determined according to the required thickness of the copper-clad laminate, and one or more prepregs can be used.
[0082] The metal foil may be copper foil or aluminum foil, and its material is not limited; the thickness of the metal foil is not particularly limited, such as 5 μm, 8 μm, 12 μm, 18 μm, 35 μm or 70 μm.
[0083] The present invention also provides an insulating plate, which comprises at least one of the aforementioned prepreg sheets.
[0084] The present invention also provides an insulating film, which comprises a carrier film and the aforementioned resin composition coated thereon, and can significantly improve the heat resistance of the insulating film.
[0085] The preparation method of the insulating film is as follows: dissolving the resin composition with a solvent to prepare a resin composition glue solution, then coating the resin composition glue solution on a carrier film, and heating and drying the carrier film coated with the resin composition glue solution to obtain the insulating film.
[0086] In a specific embodiment, the carrier film coated with the resin composition glue is baked at 100° C. to 160° C. for 3 min to 10 min, and the insulating film can be obtained after drying.
[0087] The solvent is selected from at least one of acetone, butanone, methyl isobutyl ketone, N,N-dimethylformamide, N,N-dimethylacetamide, ethylene glycol methyl ether, propylene glycol methyl ether, benzene, toluene, xylene and cyclohexane.
[0088] The carrier film is selected from at least one of PET film, PP film, PE film and PVC film.
[0089] The present invention also provides a circuit substrate, which includes one or more of the aforementioned prepreg, copper-clad laminate, insulating plate, and insulating film.
[0090] The present invention also provides an electronic device, which includes the aforementioned circuit substrate.
[0091] The present invention will be described in detail below with reference to specific embodiments; of course, it is to be understood that the embodiments of the present invention are not limited to these embodiments.
[0092] Examples 1 to 4 and Comparative Examples 1 to 4:
[0093] The components and contents of the resin compositions of Examples 1 to 4 and Comparative Examples 1 to 4 are shown in Table 1 below:
[0094] Table 1
[0095]
[0096]
[0097] Specifically, the information of each component involved in Table 1 above is shown in Table 2 below:
[0098] Table 2
[0099]
[0100] The preparation method of the resin composition in Examples 1 to 4 and Comparative Examples 1 to 4 is as follows: according to the components and corresponding contents in Table 1, an appropriate amount of butanone is mixed, stirred and mixed, and then diluted to a resin composition glue having a solid content of 65wt%, wherein the solid content of 65wt% is calculated by weight.
[0101] The T-glass fiber cloth used as the reinforcing material was pretreated with an epoxy silane coupling agent and then immersed in the resin composition glue obtained in the above Examples 1 to 4 and Comparative Examples 1 to 4, respectively. After being soaked, it was taken out and placed in a 160° C. forced drying oven, and baked for 3 to 6 minutes to obtain the semi-cured sheets corresponding to Examples 1 to 4 and Comparative Examples 1 to 4, respectively.
[0102] Copper-clad laminates corresponding to the above-mentioned embodiments 1 to 4 and comparative examples 1 to 4 were prepared. The method for preparing the copper-clad laminate was as follows: two semi-cured sheets prepared as above were cut to 300×300 mm, and the two semi-cured sheets were stacked into a composite sheet with a certain stacking structure, and then a low-profile electrolytic copper foil with a thickness of 12 μm was placed on both sides of the composite sheet, and then placed in a vacuum hot press, and hot pressed for 1.5 hours at a pressure of 1.5 MPa and a temperature of 220°C to obtain a copper-clad laminate.
[0103] The copper-clad laminates corresponding to the above-mentioned embodiments 1 to 4 and comparative examples 1 to 4 were used to perform performance tests. Specifically, the performance evaluation method is as follows:
[0104] (1) Glass transition temperature (Tg): tested according to IPC-TM-650 2.4.24.4 using a dynamic mechanical analyzer (DMA) with a heating rate of 10°C / min and a frequency of 10 Hz;
[0105] (2) Thermal conductivity: tested using ASTM D5470-2017 method;
[0106] (3) Dk and Df: Dielectric properties at 10 GHz were measured using the plate method in accordance with IPC-TM-650 2.5.5.9;
[0107] (4) Internal substrate quality: Observe the internal substrate quality under a microscope at 300mm ╳ When there is no filler agglomeration or aggregation within the 300 mm area, it is represented as O; when there are less than 5 filler agglomerations or aggregations, it is represented as Δ; when there are more than 5 filler agglomerations or aggregations, it is represented as ╳.
[0108] The properties of the copper-clad laminates obtained using the prepregs in Examples 1 to 4 and Comparative Examples 1 to 4 are shown in Table 3 below.
[0109] Table 3
[0110]
[0111] Example 2 and Comparative Example 1 were compared in parallel. The silicon nitride inorganic filler and the calcium titanate inorganic filler in Comparative Example 1 were not treated, and the components could not be mixed to form a resin composition glue and could not be used; while the silicon nitride inorganic filler in Example 2 was surface-treated with a styrene-based silane coupling agent, and the calcium titanate inorganic filler was surface-treated with a methacrylate-based agent. The copper-clad laminate prepared from the resin composition in Example 2 met the requirements of high dielectric constant, high thermal conductivity, high heat resistance, and low Df, and can be well used in the field of high heat-resistant high-frequency antenna substrate modules, especially can meet the requirements of millimeter wave antenna modules.
[0112] Example 2 is compared with Comparative Example 2 in parallel. The filler used in Comparative Example 2 is a common silica inorganic filler, while the silicon nitride inorganic filler in Example 2 is surface treated with a styrene-based silane coupling agent, and the calcium titanate inorganic filler is surface treated with a methacrylate-based filler. By comparison, it can be seen that the copper-clad laminate prepared from the resin composition in Example 2 has a higher dielectric constant and higher thermal conductivity, and can be well used in the field of high-heat-resistant high-frequency antenna substrate modules, especially meeting the requirements of millimeter-wave antenna modules.
[0113] Example 2 was compared in parallel with Comparative Example 4. The silicon nitride inorganic filler used in Comparative Example 4 was surface-treated with a styrene-based silane coupling agent, and the calcium titanate inorganic filler was not surface-treated, so the dispersibility was poor. The silicon nitride inorganic filler in Example 2 was surface-treated with a styrene-based silane coupling agent, and the calcium titanate inorganic filler was surface-treated with a methacrylate-based agent, so the dispersibility was good, and the corresponding internal substrate quality met the requirements. At the same time, it can be seen from the comparison that the copper-clad laminate prepared from the resin composition in Example 2 has a higher dielectric constant, a higher thermal conductivity, and a lower Df, and can be well used in the field of high heat-resistant high-frequency antenna substrate modules, especially can meet the requirements of millimeter wave antenna modules.
[0114] Example 3 and Comparative Example 3 were compared in parallel. The difference between Example 3 and Comparative Example 3 is that the types of polyphenylene ether resins are different. Example 3 uses a polyphenylene ether resin containing double bonds, which has good compatibility with the inorganic filler surface-treated with a double-bond silane coupling agent. However, Comparative Example 3 uses a hydroxyl-containing polyphenylene ether resin, which has poor compatibility with the inorganic filler surface-treated with a double-bond silane coupling agent, affecting various properties such as substrate quality.
[0115] Compared with Example 1 and Example 4, hydrocarbon resin is added in Example 4, so the copper clad laminate prepared from the resin composition corresponding to Example 4 has a lower Df value.
[0116] It can be seen that in the resin composition of the present invention, nitrogen-based inorganic compounds and titanate-based inorganic compounds surface-treated with silane coupling agents are added to the high heat-resistant double-bond polyphenylene ether resin system, which can further improve the thermal conductivity and Dk value (dielectric constant) of the resin composition on the basis of improving the compatibility between the components and the dispersibility of the inorganic filler in the resin system; at the same time, the use of two inorganic fillers of different types in combination can not only increase the filling amount of the inorganic filler, but also inhibit the decrease in the Dk value and thermal conductivity of the resin composition, and obtain a resin composition with excellent high heat resistance, high Dk, and high thermal conductivity, thereby finally obtaining a cured product with high heat resistance, high thermal conductivity, and high dielectric constant, thereby obtaining a cured product with relatively excellent comprehensive performance, which can be well used in the field of high heat-resistant high-frequency antenna substrate modules, especially meeting the requirements of millimeter wave antenna modules.
[0117] It should be understood that although this specification is described according to implementation modes, not every implementation mode contains only one independent technical solution. This description of the specification is only for the sake of clarity. Those skilled in the art should regard the specification as a whole. The technical solutions in each implementation mode may also be appropriately combined to form other implementation modes that can be understood by those skilled in the art.
[0118] The series of detailed descriptions listed above are only specific descriptions of feasible implementation methods of the present invention. They are not intended to limit the scope of protection of the present invention. Any equivalent implementation methods or changes that do not deviate from the technical spirit of the present invention should be included in the scope of protection of the present invention.
Claims
1. A resin composition, characterized in that include: Double bond-containing polyphenylene ether resin: 100 parts by weight; Cross-linking agent: 5-80 parts by weight; Inorganic filler: 10-250 parts by weight, wherein the inorganic filler is a mixture of a titanate inorganic compound and an inorganic nitrogen-containing compound, wherein the titanate inorganic compound is a titanate inorganic compound surface-treated with a silane coupling agent, and the nitrogen inorganic compound is a nitrogen inorganic compound surface-treated with a silane coupling agent, and the silane coupling agent contains a vinyl group, an allyl group, a methacrylate group or an acrylate group; Hydrocarbon resin: 0-60 parts by weight.
2. The resin composition according to claim 1, characterized in that: The titanate inorganic compound is selected from at least one of calcium titanate, strontium titanate, barium titanate, lead titanate, magnesium titanate, lead zirconate titanate, and lanthanum lead zirconate titanate.
3. The resin composition according to claim 1, characterized in that: The inorganic nitrogen-containing compound is selected from at least one of aluminum nitride, boron nitride and silicon nitride.
4. The resin composition according to claim 1, characterized in that: The silane coupling agent for treating the titanate-based inorganic compound and the silane coupling agent for treating the nitrogen-based inorganic compound contain the same reactive group.
5. The resin composition according to claim 1, characterized in that: The silane coupling agent is at least one of the following structures:
6. The resin composition according to claim 1, characterized in that: The D50 of the inorganic nitrogen-containing compound is 3 μm-20 μm, and the D50 of the titanate-based inorganic compound is 0.1 μm-5 μm; or, the D50 of the inorganic nitrogen-containing compound is 5 μm-10 μm, and the D50 of the titanate-based inorganic compound is 1 μm-5 μm.
7. The resin composition according to claim 1, characterized in that: The hydrocarbon resin is selected from at least one of polybutadiene, polybutadiene-styrene copolymer, divinylbenzene, styrene, BVPE, butadiene / divinylbenzene / styrene copolymer, butadiene / divinylbenzene copolymer and divinylbenzene / BVPE copolymer.
8. The resin composition according to claim 1, characterized in that: The double-bond-containing polyphenylene ether resin and the silane coupling agent contain the same unsaturated double-bond group.
9. The resin composition according to claim 1, characterized in that: The crosslinking agent is selected from at least one of triallyl isocyanate monomers, triallyl isocyanate prepolymers, butadiene monomers, styrene monomers, pentadiene monomers, dicyclopentadiene dimethacrylate monomers, norbornene monomers, and cyclopentadiene monomers.
10. Use of the resin composition according to any one of claims 1 to 9 in prepregs, copper-clad laminates, insulating films, insulating boards, circuit substrates and electronic devices.